The rainforest grew all around - Mitchell, Susan K. (Sylvan Dell Pub., 2007)
The jungle comes alive as children learn about a wide variety of animals and plants living in the Amazon rainforest, in this adaptation of the song "The green grass grew all around." Includes "For Creative Minds" section with animal and plant adaptation facts and a recipe.